Prognostic gene expression analysis in a retrospective, multinational cohort of 155 multiple myeloma patients treated outside clinical trials. (26th August 2021) - Chen, Yan‐Ting; Valent, Erik T.; van Beers, Erik H.; Kuiper, Rowan; Oliva, Stefania; Haferlach, Torsten; Chng, Wee‐Joo; van Vliet, Martin H.; Sonneveld, Pieter; Larocca, Alessandra
Abstract: Objectives: Typically, prognostic capability of gene expression profiling (GEP) is studied in the context of clinical trials, for which 50%‐80% of patients are not eligible, possibly limiting the generalizability of findings to routine practice. Here, we evaluate GEP analysis outside clinical trials, aiming to improve clinical risk assessment of multiple myeloma (MM) patients. Methods: A total of 155 bone marrow samples from MM patients were collected from which RNA was analyzed by microarray. Sixteen previously developed GEP‐based markers were evaluated, combined with survival data, and studied using Cox proportional hazard regression. Results: Gene expression profiling‐based markers SKY92 and the PR‐cluster were shown to be independent prognostic factors for survival, with hazard ratios and 95% confidence interval of 3.6 [2.0‐6.8] ( P  < .001) and 5.8 [2.7‐12.7] ( P  < .01) for overall survival (OS). A multivariate model proved only SKY92 and the PR‐cluster to be independent prognostic factors compared to cytogenetic high‐risk patients, the International Staging System (ISS), and revised ISS. A substantial number of high‐risk individuals could be further identified when SKY92 was added to the cytogenetic, ISS, or R‐ISS. In the cytogenetic standard‐risk group, ISS I/II, and R‐ISS I/II, 13%, 23%, and 23% of patients with adverse survivals were identified. Conclusions: For the first time, this study confirmed the prognostic value of GEP markers outside clinical trials. Conventional prognostic models to define high‐risk MM are improved by the incorporation of GEP markers.